Comparison of Bacterial Adherence on Different Archwires after Clinical Use - Syed Ashique Abdulhameed; Nakul N. Mude; Divya Chandrasekaran; Dwijesh S. Goswami; Omar Naif Almutairi; Priya Manimegalan (Journal of Pharmacy and Bioallied Sciences)
Background: An essential component of orthodontic therapy, orthodontic archwires may operate as surfaces for bacterial adhesion, which might result in issues with oral health. Materials and Methods: This study assessed the bacterial adhesion to three different kinds of orthodontic archwires: beta-titanium (TMA), nickel-titanium (NiTi), and stainless steel (SS). At the conclusion of the clinical usage period, samples of each kind of archwire were gathered and submitted to microbiological investigation in order to determine the quantity of adhering bacterial colonies. Using scanning electron microscopy (SEM), the surface properties of the archwires were evaluated after usage. Results: The three kinds of archwires had significantly different rates of bacterial adhesion, according to the findings. With an average of 1500 ± 50 CFU/mm2, SS archwires showed the highest level of bacterial adhesion, followed by NiTi archwires at 1100 ± 45 CFU/mm2. The least amount of bacteria adhered to TMA archwires, with an average of 800 ± 30 CFU/mm2. According to SEM pictures, the degree of bacterial adhesion was associated with the archwires’ surface roughness, with smoother surfaces showing less bacterial colonization. Conclusion: In comparison with SS and NiTi archwires, the research finds that TMA archwires are linked to the least amount of bacterial adhesion.